Teaching Georgian Language To Georgians Living Abroad At Present Most New Problems - Putkaradze, Tariel (Yearbook of Kutaisi Ilia Chavchavadze Public Library, 2022)
Approximately four million Georgians living across the present day borders of Georgia nowadays. They can be represented in several groups: Autochthon Georgians in Turkey and Azerbaijan ( Tao-Klarjeti, Lazeti, Saingilo); Descendants of Georgians deported in Iran (Phereidan, Ispahan) 400 years ago Descendants of Georgian Muhajirs exiled in Turkey 150 years ago Migrant Georgians left the country in 20s and 90s of 20th century. From above mentioned Georgians first three groups should be analysed in one category; Preserving their mother tongue (teaching, functioning…) should be conducted by governments of the states where they belong as citizens; of course Georgian side should take part in organizing Georgian language teaching (guide books, teachers … ). Defending linguistic rights for Georgians newly migrated in Europe, USA and Asia is the prerogative of receiving countries; first of all Georgia should be interested in teaching Georgian language to them. According to present day data, there are many reasons why learning Georgian language is problematic for all four groups, due to this fact it the urgent problem for Georgia to publish modern guide book of Georgian language for millions of Georgians living in different states, which will consider the nature of Georgian language, in particular real paradigm of noun and verb existing nowadays. Besides, new guide book should be adapted to the language and culture where the given groups live. Besides publishing guide book, it’s necessary to launch a strong web page for distance learning and plan the training for teachers. For Georgians living abroad, teaching mother tongue is the only way to retain linguistic-ethnic identity; otherwise millions of Georgians face the threat of full assimilation in the nearest future. Concerning legal status teaching Georgian abroad should be reviewed in several dimensions: 1. Teaching Georgian as mother tongue to autochthon Georgians living across the present day borders of Georgia nowadays (considering them as the representatives of diaspora won’t be the precise qualification). 2. Teaching Georgian as mother tongue to descendants of Georgians also for descendants of Muhajirs exiled in Iran long time ago; particularly in Pereidan, Mazandaran, Pars, Ispahan and Khuzistan, also in middle Turkey (Adapazar, BursaInegol, Amasia, Samsun-Patsa, Gonen, Ankara, Istanbul …). Teaching Georgian as a mother tongue to the representatives of new diasporas. Receiving country has no liability to teach mother tongue ( USA, Greece, France …), however for Georgians included in first and second groups - Autochthon Georgians and Muhajir descendants , or Georgians deported in Iran 400 hundred years ago - according to international standards relevant states have certain responsibility to teach Georgian language.